Imprinting of metal receptors into multilayer polyelectrolyte films: fabrication and applications in marine antifouling. Issue 1 (17th October 2014) - Puniredd, Sreenivasa Reddy; Jańczewski, Dominik; Go, Dewi Pitrasari; Zhu, Xiaoying; Guo, Shifeng; Ming Teo, Serena Lay; Chen Lee, Serina Siew; Vancso, G. Julius
Abstract : Polymeric films constructed using layer-by-layer fabrication were employed as a platform for metal ion immobilization and applied as a marine antifouling coating. Abstract : Polymeric films constructed using the layer-by-layer (LbL) fabrication process were employed as a platform for metal ion immobilization and applied as a marine antifouling coating. The novel Cu 2+ ion imprinting process described is based on the use of metal ion templates and LbL multilayer covalent cross-linking. Custom synthesized, peptide mimicking polycations composed of histidine grafted poly(allylamine) (PAH) to bind metal ions, and methyl ester containing polyanions for convenient cross-linking were used in the fabrication process. Two methods of LbL film formation have been investigated using alternate polyelectrolyte deposition namely non-imprinted LbLA, and imprinted LbLB . Both LbL films were cross linked at mild temperature to yield covalent bridging of the layers for improved stability in a sea water environment. A comparative study of the non-imprinted LbLA films and imprinted LbLB films for Cu 2+ ion binding capacity, leaching rate and stability of the films was performed. The results reveal that the imprinted films possess enhanced affinity to retain metal ions due to the preorganization of imidazole bearing histidine receptors. As a result the binding capacity of the films for Cu 2+ could be improved by seven fold. Antifouling properties of the resulting materials in a marine environment have been demonstrated against the settlement of barnacle larvae, indicating that controlled release of Cu ions was achieved.